Management Strategy of Islamic Education Institution - Din Muhammad Zakariya; Masyhad BH (Studia Religia : Jurnal Pemikiran dan Pendidikan Islam, 2020)
As a national education subsystem, Islamic education should participate contribute in building and improving the quality of Indonesian people with creating the best generation (khairunnas / goden generation), which is the generation with high achievements in science and technology and be able to practice it in everyday life. This study aims to discuss the management strategies of Islamic educational institutions. This type of research is library research, namely research whose main object is books or other sources of literature. In this paper two strategies are offered management namely general strategies and specific strategies. Strategies are generally offered based on the Sirozi concept which includes substantive, bottom-up, deregulatory, and strategy cooperative. Whereas specifically the implementation of Islamic Education Management functions (planning, organizing, implementing / directing and supervising) comprehensive and consistently valued as smart and futuristic strategic steps.